Pharmaceutical hemostasis at peptic ulcer bleeding: state-of-the-art and perspectives - A. A. Schegolev; O. A. Al Sabunchi; S. A. Valetov; A. V. Pavlychev; Ye. A. Klochneva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study efficacy of parenteral proton pump inhibitors in patients with ulcerative gastroduodenal bleeding.Material and methods. Overall 71 patients were included in original study. Patients of the first group (n=30) received antisecretory treatment by parenteral omeprazole, the second group (n=41) — tablet form of the same preparation.Results. In the first group no relapses of bleeding or mortality was detected, in the second group in 4 (10%) patients there was relapse of bleeding, that allows to assume higher efficacy of therapeutic hemostasis by the parenteral form of proton pump inhibitors within complex therapy.Conclusions. Application of Omez, lyophilizate for infusions, allows to improve treatment results in patients of the main group, reduces risk of hemorrhage relapse and, therefore mortality and urgent surgery rates.